# What is the slope and y-intercept of the equation 3(y − 2) + 6(x + 1) − 2 = 0? A. slope = -2, y-intercept = B. slope = 2, y-intercept = C. slope = -2, y-intercept = D. slope = 2, y-intercept = E. slope = -2, y-intercept = Reset Next

Step-by-step explanation:

Carrying out the indicated multiplication, we get

3y - 6 + 6x + 6 - 2 = 0.

Combining like terms, we get 3y = -6x + 2.

Solving for y:  y = -2x + 2/3.

The slope is -2 and the y-inercept is 2/3.

## Related Questions

If 4x=32 find the value of 33-5x

The answer to this question is -7

-7

Step-by-step explanation:

32/4=8

x=8

33-5*8

33-40

-7

25 points!

I don't need an answer, just an explanation of how to do it. 1-(-3)

Step-by-step explanation:

When you are subtracting a negative number from a positive number, the negative - sign will always turn into a positive + sign.

So in this case, you would cancel out the negative - signs and put in a positive + sign:   1-(-3)  -->  1+3

When you are subtracting a negative number from a positive number, the negative - sign will always turn into a positive + sign.

So in this case, you would cancel out the negative - signs and put in a positive + sign:   1-(-3)  -->  1+3

How do you do this problem and please show the work? 3/4 (4-x)

(3/4*4)+(3/4*-x)= (3)+(-3/4x) = -3/4x+ 3

A pharmacist has 18% bleach solution. How much of this solution and how much water must be mixed together to make 10 liters of a 12% solution?